Self-assembly of luminescent 42-metal lanthanide nanowheels with sensing properties towards metal ions and nitro explosives. Issue 43 (17th October 2019) - Shi, Dongliang; Yang, Xiaoping; Chen, Hongfen; Ma, Yanan; Schipper, Desmond; Jones, Richard A.
Abstract : Two 42-metal lanthanide nanowheels [Ln42 L14 (OH)28 (OAc)84 ] (Ln = Yb (1 ), Sm (2 )) with a NIR luminescent response towards metal ions and nitro explosives were constructed. Abstract : Two 42-metal lanthanide wheel-like nanoclusters 1 and 2 were successfully constructed from a tridentate vanillin ligand. The external and internal diameters of the wheels in the clusters are about 3.6 nm and 1.5 nm, respectively. The vanillin ligand exhibits a μ2 (η 1 :η 2 :η 1 ) coordination mode in the structures of the clusters. In the solid state, 1 and 2 have open 3D channel structures. Upon excitation in the ligand absorption bands, 1 and 2 exhibit typical NIR luminescence of Yb 3+ and visible emission of Sm 3+, respectively. Interestingly, 1 shows lanthanide luminescent sensing towards metal ions and nitro explosives, especially to Cu 2+, Cd 2+ and 2-NP at the ppm level.